2022
DOI: 10.1021/acs.jmedchem.2c00812
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Structure–Activity Relationships at the Orthosteric Binding Site of P2X Ion Channels: The Route to Selectivity

Abstract: The orthosteric ATP-binding site of the P2X receptors is poorly understood. Only a few compounds were well characterized for their P2X receptor functional activity and subtype selectivity. This study represents the first fully functional characterization of various ATP derivatives combined with in silico studies to advance the understanding of SARs at the orthosteric binding sites of P2X receptors leading to the identification of 2-chloro-3-trifluoromethylbenzoyl ATP ester as a novel pan-P2X receptor agonist a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Therefore, compounds 21 were tested at 1 μM in radioligand displacement experiments against four subtypes of adenosine receptors, namely, A 1 , A 2A , A 2B , and A 3 , as previously reported ( Figure S7 and Table S3 , Supporting Information ). 55 In addition, compounds were screened at 10 μM against P2X7R purinergic receptors in an YO-PRO-1 uptake assay 56 ( Figure S8 , Supporting Information ). Performed experiments, however, revealed that synthesized 5,6-dihydro-5-azapurines 21 have little to no affinity/inhibitory activity toward these five purinergic receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, compounds 21 were tested at 1 μM in radioligand displacement experiments against four subtypes of adenosine receptors, namely, A 1 , A 2A , A 2B , and A 3 , as previously reported ( Figure S7 and Table S3 , Supporting Information ). 55 In addition, compounds were screened at 10 μM against P2X7R purinergic receptors in an YO-PRO-1 uptake assay 56 ( Figure S8 , Supporting Information ). Performed experiments, however, revealed that synthesized 5,6-dihydro-5-azapurines 21 have little to no affinity/inhibitory activity toward these five purinergic receptors.…”
Section: Resultsmentioning
confidence: 99%
“…The P2XR assays were performed as previously described by Isaak et al [23] ACKNOWLEDGMENTS Anna Junker thanks the German Research Foundation (DFG) for the financial support (JU 2966/2-1). Anna Junker, Petra Hundehege, Guiscard Seebohm, and Thomas Budde thank the German Research Foundation (DFG) for the financial support (GRK2515/1-1, BU1019/ 16-1).…”
Section: Contraction Analysismentioning
confidence: 99%